PENGARUH PAJAK HIBURAN DAN PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH KOTA BANDUNG - Eko Purwanto (LPPM UNIBI, 2018)
This study aims to determine the effect of entertainment taxes and hotel taxes on the original revenue area of Bandung. This research was conducted with the type of quantitative research using descriptive method. The population in this study is the original revenue of Bandung city with sample of Entertainment Tax Reception and Hotel Tax for the period of 2011 until 2016. Data collection technique used is documentation BPPD Bandung to get secondary data. The results of this study show that Entertainment Tax negatively affect the original income area of Bandung city because tcount is smaller than ttable that is equal to -0.926 < 4.30265 so that in accordance with the hypothesis testing criteria is H0 accepted and and Ha rejected and hotel tax affects the city's original revenue Bandung because tcount bigger than ttable that is equal to 9,684 > 4,30265 with criterion of hypothesis test is H0 rejected and and Ha accepted. Hotel entertainment and tax taxes simultaneously affect the city's original income of Bandung because Fcount is bigger than Ftable that is equal to 88.991 > 2,920.. Keywords: Entertainment Tax, Hotel Tax, Local Revenue